ANALISIS PENGENDALIAN PERSEDIAAN BERAS DI PT. DAYA TANI SEMBADA KABUPATEN NGAWI - Hastuti, Dhiana Putri; Mubarokah, Mubarokah; Syah, Mirza Andrian (Yayasan Education and Social Center, 2023)
The demand for rice fluctuates significantly along with the increase in population every year, making PT. Daya Tani Sembada, as a premium rice-producing company, must do planning to deal with changes in demand that will occur. This research aims to analyze rice demand forecasting and the optimal rice inventory. The method of determining the sample is purposive sampling, where the Director and Administrative Staff are vital informants. Demand forecasting was analyzed using the Double Exponential Smoothing (Holts) method and inventory control using Economic Order Quantity. The results showed that: 1) forecasting calculations show that the demand for rice in the next period is 33,367.38 tons; 2) inventory control calculations show that the company can prepare premium rice inventory of 29.89 tons, safety stock of 336.03 tons, ROP when rice inventory is at 779.47 tons, and TIC that must prepare amounting to IDR. 5,357,082,020, -, overall, demand for rice has increased by 8,662.58 tons from the previous period so that the company can increase production for the next period by the draft inventory control calculation